Marketing Strategies for Hajj and Umrah Products from a Performance Marketing Perspective: A Case Study of PT Wuhi Tour Bengkulu - Karien Nabila Ayu; Khairiah Elwardah; Khozin Zaki (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
Competition in the Hajj and Umrah travel business is getting tougher along with the development of digital technology, so companies are required to implement measurable and effective marketing strategies. This study aims to analyze the performance of marketing strategies, describe the results of the SWOT analysis, and identify supporting and inhibiting factors at PT. Wuhi Tour Bengkulu. The method used is descriptive qualitative through in-depth interviews, observation, and documentation with the Director and staff of PT. Wuhi Tour Bengkulu. The results show that the marketing performance strategy is implemented through three stages: planning by segmenting prospective pilgrims based on age, economic conditions, and readiness to worship; implementation through multi-channel marketing using digital and conventional media with personal follow-up; and measurement based on the number of inquiries, registrations, and growth of pilgrims per period. The SWOT analysis shows strengths in the partner network and service quality, weaknesses in social media content, opportunities from digital developments, and threats of price competition. Inhibiting factors include economic conditions and the mindset of prospective pilgrims who prioritize low prices. This strategy has been implemented in a structured manner, but needs to improve the quality of digital content and consistency in communicating service values ​​to increase the conversion of Hajj pilgrims sustainably.